Economic Performance in the Arab Maghreb Union (AMU): A Focus on the Contributions of Economic Openness and Institutional Quality - Chile Nzeh, Innocent; Uzoechina, I Benedict; Okoli, Uju Victoria; Imoagwu, Chika P (FEB - Universitas Lampung, 2023)
Empirical results have shown that economic openness and institutional quality variables influence the performance of the economy of different countries and regions differently. While these variables improve the economy of some countries and regions, findings have shown that in others the reverse is the case. In this present study, emphasis is on the contributions of economic openness and institutional quality to the economic performance of the Arab Maghreb Union (AMU). The study utilized the panel autoregressive distributed lag (ARDL) model with annual series ranging from 2000 to 2020. Institutional quality variables were selected using the principal component analysis (PCA). The short run results showed that, while capital account openness impacted positively on GDP per capita, trade openness adversely affected GDP per capita. In the long run, results indicated that FDI inflows had a positive and significant impact on GDP per capita. In the long run also, while governance effectiveness had negative and significant impact on GDP per capita, the impact of political stability was positive and significant. Consequently, the study recommends that in the short run, economic liberalization policy in the bloc should focus more on capital account openness than trade openness, while the long run policy thrust should centre on how to attract and harness FDI inflows into the member countries. This requires improvement in governance through building strong and virile institutions.